4
$\begingroup$

If $ \alpha_i, i=0,1,2...n-1 $ be the nth roots of unity, the $\sum_{i=0}^{n-1} \frac{\alpha_i}{3- \alpha_i}$ is equal to?

A) $ \frac{n}{3^n-1} $ B) $ \frac{n-1}{3^n-1} $ C) $ \frac{n+1}{3^n-1} $ D) $ \frac{n+2}{3^n-1} $

Attempt: I know that $(3- \alpha_0)(3- \alpha_1)....(3-\alpha_{n-1})= (3^n-1)/2 $

But I have no clue about the numerator. Adding 3 and subracting 3 from the numberator would make the fraction simpler, but I would still have to sum up $ 1/(3- \alpha_i) $

$\endgroup$
  • $\begingroup$ Since options are given we can solve this by simply considering $n=1$. Here $a_1=1$ and the sum is $1/2$ and the four options for $n=1$ says a)1/2 b) 0 c) 1 d) 3/2. $\endgroup$ – Winther Dec 4 '16 at 17:36
4
$\begingroup$

Let $\dfrac{a_i}{3-a_i}=b_i\iff a_i=\dfrac{3b_i}{1+b_i}$

As $a_i^n=1,$

$$\left(\dfrac{3b_i}{1+b_i}\right)^n=1\iff(3^n-1)b_i^n-\binom n1b_i^{n-1}+\cdots=0$$

By Vieta's formula,

$$\displaystyle\sum_{i=0}^{n-1}b_i=\dfrac{\binom n1}{3^n-1}$$

$\endgroup$
3
$\begingroup$

$$\frac{u}{3-u}=\frac{3}{3-u}-1$$

So your sum is:

$$-n+3\sum \frac{1}{3-a_i}$$

Letting $p(x)=x^n-1$, show that $\frac{p'(x)}{p(x)}=\sum \frac{1}{x-a_i}$.


More generally, if $p(x)=(x-b_1)(x-b_2)\cdots (x-b_n)$ then $$\sum \frac{b_i}{b-b_i} = -n + b\frac{p'(b)}{p(b)}$$

$\endgroup$
  • $\begingroup$ Can you please elaborate on the last step? $\endgroup$ – Shashank Dec 4 '16 at 17:19
  • $\begingroup$ Take $\log p(x) = \log(x-a_1)+\log(x-a_2)+\dots$ and take the derivative of ech side. @Shashank $\endgroup$ – Thomas Andrews Dec 4 '16 at 17:21
  • $\begingroup$ That will be useful. Thanks! $\endgroup$ – Shashank Dec 4 '16 at 23:55
1
$\begingroup$

(For future reference.) Introducing

$$f(z) = \frac{z}{3-z} \frac{nz^{n-1}}{z^n-1}$$

we get

$$S_n = \sum_{q=0}^{n-1} \frac{\exp(2\pi i q/n)}{3-\exp(2\pi i q/n)} = \sum_{q=0}^{n-1} \mathrm{Res}_{z=\exp(2\pi i q/n)} f(z).$$

Residues sum to zero so we have

$$S_n + \mathrm{Res}_{z=3} f(z) + \mathrm{Res}_{z=\infty} f(z) = 0$$

Observe that

$$\mathrm{Res}_{z=3} f(z) = - \frac{n3^n}{3^n-1}$$

and

$$\mathrm{Res}_{z=\infty} f(z) = -\mathrm{Res}_{z=0} \frac{1}{z^2} f(1/z) \\ = -\mathrm{Res}_{z=0} \frac{1}{z^2} \frac{1/z}{3-1/z} \frac{n/z^{n-1}}{1/z^n-1} \\ = -\mathrm{Res}_{z=0} \frac{1}{z^2} \frac{1}{3z-1} \frac{nz}{1-z^n} \\ = -\mathrm{Res}_{z=0} \frac{1}{z} \frac{1}{3z-1} \frac{n}{1-z^n} = n.$$

Hence

$$S_n - \frac{n3^n}{3^n-1} + n = 0$$

or

$$S_n = \frac{n3^n-n(3^n-1)}{3^n-1} = \frac{n}{3^n-1}.$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.